The impact of clinical competency test on dental students' clinical skills learning and patient care - Mohd Yusof, Zamros Yuzadi; Hong, Teng Ching; Saub, Roslan; Gonzalez, Maria Angela G.; Esa, Rashidah; Che Ab Aziz, Zeti Adura (2017)
Clinical Competency Test (CCT) has been regarded as the contemporary method to assess dental students' clinical skills in integrated dental curriculum in dental schools worldwide. It is an independent test for students to carry out specific clinical procedures on patients in the clinic. Each year, students are required to undertake CCTs on different clinical procedures based on the levels of clinical skills relevant to that year (Year 111 -V) . As dentistry Is a clinical profession, students are required to pass all CCTs In the respective year before they are eligible to sit for final examinations. Otherwise, they will be required to repeat the year. In UM, students sit for five CCTs In Year Ill, four CCTs In Year IV, and six CCTs In Year V.